Activity profiles in international women`s team handball using playerload - Wik, E. H.; Luteberget, L. S.; Spencer, M. (International Journal of Sports Physiology and Performance, 2017)
Team handball matches place diverse physical demands on players, which may result in fatigue and decreased activity levels. However, previous speed-based methods of quantifying player activity may not be sensitive for capturing short-lasting team-handball-specific movements. Purpose: To examine activity profiles of a women`s team handball team and individual player profiles, using inertial measurement units. Methods: Match data were obtained from 1 women`s national team in 9 international matches (N = 85 individual player samples), using the Catapult OptimEye S5. PlayerLoad/min was used as a measure of intensity in 5- and 10-min periods. Team profiles were presented as relative to the player`s match means, and individual profiles were presented as relative to the mean of the 5-min periods with >60% field time. Results: A high initial intensity was observed for team profiles and for players with =2 consecutive periods of play. Substantial declines in PlayerLoad/min were observed throughout matches for the team and for players with several consecutive periods of field time. These trends were found for all positional categories. Intensity increased substantially in the final 5 min of the first half for team profiles. Activity levels were substantially lower in the 5 min after a player`s most intense period and were partly restored in the subsequent 5-min period. Discussion: Possible explanations for the observed declines in activity profiles for the team and individual players include fatigue, situational factors, and pacing. However, underlying mechanisms were not accounted for, and these assumptions are therefore based on previous team-sport studies.